BIOLOGY AND MANAGEMENT OF PURPLE NUTSEDGE (CYPERUS ROTUNDUS L.) - J. Iqbal; S. Hussain; A. Ali; A. Javaid (Journal of Animal and Plant Sciences, 2012)
Pot trials were conducted using a completely randomized design to investigate the effect of fertilizers, population density, growing period and temperature on viability of purple nutsedge (Cyperus rotundus L.) tubers, and the effect of herbicides on re-generation of tubers. Increase in nitrogen and phosphorus fertilizer rates enhanced shoot biomass by 59-961%, underground biomass by 21–279%, tubers numbers by 50–579% and tubers biomass by 21–348%. Individual tuber’s weight was, however, decreased by fertilizers application. By increasing growth period [15, 30, …, 75 days after sowing (DAS)] shoot density was increased by 50–850%, shoot biomass by 99–403%, under ground biomass by 10–649%, tuber numbers by 39–1122%, and tubers biomass per pot by 22–982% as compared to the first record of the data (15 DAS). In population density trials, shoot length, shoot and underground biomass, number of tubers per pot and tubers weight were significantly increased up to 15 tubers per pot and deceased thereafter. Drying of tubers in hot sun (42±3 °C) for four days completely lost their viability. Tubers viability was significantly decreased up to three hours freezing, and no sprouting was recorded thereafter. Application of glyphosate (Round up 490GL) and paraquat (Gramoxone) completely killed the above ground growth and reduced the tuber’s viability by 89% and 32%, respectively, as compared to control. Present study concludes that purple nutsedge can effectively be managed by herbicide glyphosate as well as by exposing the tubers to sun during hot months of May and June.
Keywords: Biology; Cyperus rotundus; management; purple nutsedge; weed biology